Beyond the lab: a rewarding experience in Melbourne / Aisyah Jaafar - Jaafar, Aisyah (Faculty of Pharmacy, 2024)
As a PhD candidate (Pharmacology) at the Faculty of Pharmacy, UiTM, supervised by Prof. Dr. Mizaton Hazizul Hasan, I had the honour of presenting my research at the ASCEPT, APFP and APSA Joint Congress held in Melbourne, Australia, earlier this month. This opportunity marked a wonderful and impactful milestone in my academic journey.